2020
DOI: 10.3390/molecules26010097
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed C–H Arylation of Benzofurans with Triarylantimony Difluorides for the Synthesis of 2-Arylbenzofurans

Abstract: Pd-catalyzed regioselective C–H arylation is a useful tool for the chemical modification of aromatic heterocycles and 2-arylbenzofuran derivatives are of interest as biologically active substances. Herein, the reaction of triarylantimony difluorides with benzofurans under aerobic conditions in 1,2-DCE, using 5 mol% Pd (OAc)2 and 2 eq. of CuCl2 at 80 °C, produced a variety of 2-arylbenzofurans in moderate-to-high yields. The reaction is sensitive to the electronic nature of the substituents on the benzene ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Deuterated substrate 1a-D was treated under the standard conditions (Scheme -ii), and no deuterium scrambling was observed in product 1a , suggesting that a reversible concerted metalation–deprotonation process is unlikely to occur in the reaction. ,,, Furthermore, a kinetic isotope effect (KIE) study was conducted, and the small magnitude of KIE (1.17) showed that the cleavage of the C–H bond is unlikely to be involved in the rate-determining step (Scheme -iii). ,,, Beyond the CMD mechanism, an S E Ar mechanism at the C-2 site of benzofuran followed by reductive elimination and rearomatization ,,, or an electrophilic attack of cationic palladium followed by aryl ligand migration seem more likely to be responsible for the reaction, which is consistent with the results of deuterium scrambling and the KIE studies. In addition, the Heck-type mechanism might also be possible, as demonstrated by many others. ,,,,,, Finally, although we cannot rule out the possibility of the Pd 3 cluster acting as a reservoir to in situ generate some mononuclear Pd species or nanoparticles, the ultraviolet–visible (UV–vis) spectra of the solution in the reaction process (Scheme -iv) showed that the Pd 3 Cl absorption spectrum remained essentially unchanged over the reaction course, indicating that the Pd 3 cluster core might not undergo substantial change or decomposition during catalysis.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Deuterated substrate 1a-D was treated under the standard conditions (Scheme -ii), and no deuterium scrambling was observed in product 1a , suggesting that a reversible concerted metalation–deprotonation process is unlikely to occur in the reaction. ,,, Furthermore, a kinetic isotope effect (KIE) study was conducted, and the small magnitude of KIE (1.17) showed that the cleavage of the C–H bond is unlikely to be involved in the rate-determining step (Scheme -iii). ,,, Beyond the CMD mechanism, an S E Ar mechanism at the C-2 site of benzofuran followed by reductive elimination and rearomatization ,,, or an electrophilic attack of cationic palladium followed by aryl ligand migration seem more likely to be responsible for the reaction, which is consistent with the results of deuterium scrambling and the KIE studies. In addition, the Heck-type mechanism might also be possible, as demonstrated by many others. ,,,,,, Finally, although we cannot rule out the possibility of the Pd 3 cluster acting as a reservoir to in situ generate some mononuclear Pd species or nanoparticles, the ultraviolet–visible (UV–vis) spectra of the solution in the reaction process (Scheme -iv) showed that the Pd 3 Cl absorption spectrum remained essentially unchanged over the reaction course, indicating that the Pd 3 cluster core might not undergo substantial change or decomposition during catalysis.…”
Section: Resultsmentioning
confidence: 72%
“…In addition, the Heck-type mechanism might also be possible, as demonstrated by many others. 57,59,60,63,64,68,74 Finally, although we cannot rule out the possibility of the Pd 3 cluster acting as a reservoir to in situ generate some mononuclear Pd species or nanoparticles, the ultraviolet−visible (UV−vis) spectra of the solution in the reaction process (Scheme 3-iv) showed that the Pd 3 Cl absorption spectrum remained essentially unchanged over the reaction course, 31 indicating that the Pd 3 cluster core might not undergo substantial change or decomposition during catalysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of palladium lies in its unique ability to adsorb hydrogen and catalyse hydrogenation and dehydrogenation reactions. Palladium plays a fundamental role in a wide range of applications: in the energy field for the production [1], storage [2] and use of hydrogen in catalytic fuel cells [3][4][5], and even in the chemical synthesis field with applications in optoelectronics [6] and biology [7,8]. It is estimated that it is the element with the highest hydrogen adsorption capacity, managing to store volumes equal to 935 times its own [9].…”
Section: Introductionmentioning
confidence: 99%